Mental Strength of Football Players When Matching: Case Study on Village League Teams Karyamukti Village - Mohammad Ramdani, Fajar; Angga Permadi, Asep; Ramadhana Sonjaya, Azhar; Izwan Shahril, Mohd (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. This study aims to determine the level of mental toughness of players when competing, this is because one aspect of the team's success is that the players have mental toughness. Materials and methods. This type of research is quantitative descriptive, the population in this study were Karyamukti Village players who participated in the match in the Zone 5 Village League competition in Garut Regency, the number of teams that followed amounted to 25 teams. The sampling technique uses probability sampling. The criteria for determining this sample include: (1) Karyamukti Village players who take part in the village league, (2) are willing to be a sample, and (3) fill out the instrument provided by the researcher in full. The instrument used is Mental Toughness proposed by (Gucciardi et al., 2009). The validity index is -0.135 - 0.729 with a reliability coefficient of 0.9156. Data analysis techniques used using Microsoft Excel applications. Results. The results showed that the results obtained were: the indicator of developing through challenges with an average value of 80.8% was categorized as high, while the indicator of sports awareness with an average value of 72.0% was categorized as high, while the hard attitude indicator with an average value of 79.9% was categorized as high, and the indicator of wanting to succeed with an average value of 79.1% was categorized as high, and the overall result of the level of mental toughness of Karyamukti Village players when competing with an average result of 79.3%. Conclusion. The results were categorized as high. This shows that the hypothesis proposed in this study is accepted.